Synthesis of Carbon Nanomaterials from Polyethylene Terephthalate (PET) Waste Using Chemical Vapor Deposition - Ezani, Nor Adnin Ezani Mohd; Harun, Mohd Hamzah; Zaharuddin, Izzuddin Mohd; Othman, Norfazlinayati; Mohamed, Mahathir; Alias, Mohd Sofian; Rahman, Mohd Faizal Abd; Umar, Khairil Nor Kamal; Mudri, Nurul Huda; Halim, Khairul Azhar Abdul; Hilmi, Farah Fadzehah; Tajau, Rida (Journal of Material Science and Radiation, 2025)
Upcycling is an effective approach to reduce plastic waste, polyethylene terephthalate (PET) and promote sustainability. Plastic bottles usually were made from PET polymer and a raw material to produce carbon nanomaterials (CNMs). CNMs are synthesized using chemical vapor deposition (CVD) process and purified to eliminate catalysts and unwanted compounds. Various catalysts were used to investigate the economic and effective in producing the CNMs. Metal catalysts such as ferrocene, cobalt and iron are the important elements in the CVD process as they provide surfaces for carbon to attach. CNMs morphology and graphitic structure were observed from Raman analysis and TEM analysis. The application of upcycling offers the advantage of utilizing low-cost raw materials to produce higher-value products, providing additional benefits.